Lightning mapping: Techniques, challenges, and opportunities - Alammari A.; Alkahtani A.A.; Ahmad M.R.; Noman F.M.; Mohd Esa M.R.; Kawasaki Z.; Tiong S.K. (Institute of Electrical and Electronics Engineers Inc., 2023)
Mapping; Signal processing; Wavelet transforms; Cross correlations; Direction finder; Lightning radiations; Lightning signals; Localization and mappings; Performance and reliabilities; Technical challenges; Very high frequency; Lightning